Effect of second warm ischemia elimination on kidney graft function: an experiment and clinical study - A. V. Shabunin; P. A. Drozdov; D. A. Makeev; I. V. Nesterenko; O. S. Zhuravel; S. A. Astapovich; E. A. Lidjieva (Вестник трансплантологии и искусственных органов, 2023)
Objective: to evaluate the effectiveness of a new device for second warm ischemia (SWI) elimination in kidney transplantation (KT).Materials and methods. The study included clinical and experimental stages. The clinical stage included 63 patients out of 219 who underwent KT at Botkin Moscow City Clinical Hospital between July 2018 and August 2022. The inclusion criteria were kidneys from donation after brain death (DBD) donors with expanded criteria or kidneys from donation after circulatory death (DCD) donors, and an SWI time greater than 45 minutes. The first group consisted of 24 recipients operated on using the new SWI elimination device. The second retrospective control group consisted of 39 patients where sterile ice bags were used at the implantation stage. The groups had no statistically significant differences in the main recipient and donor characteristics, as well as in perioperative parameters. Also, from November 2021 to April 2022, 23 kidney autotransplantation experiments in female Landrace pigs were performed. The animals were cared for in accordance with the European Convention for the Protection of Vertebrate Animals used for Experimental and other Scientific Purposes (Strasbourg, 18 March 1986). Efficiency of different SWI elimination techniques was compared on two experimental models: standard donor (group 1, n = 12) and asystolic donor (group 2, n = 11).Results. In the clinical trial group, mean graft temperature (tm) before reperfusion was statistically significantly lower in group 1 using the special SWI elimination device: 6.4 ± 1.7 °C (95% CI 3.2–8.5) versus 22.1 ± 2.3 °C (18.1–24.6), р < 0.001. The risk of delayed graft function (DGF) was 3.86 times higher (95% CI 1.11–13.43) with the standard SWI elimination technique. In the experimental group, in the subgroups using the new device (n = 12), graft tm before reperfusion was 5.1 ± 0.4 °C (95% CI 4.5–5.8), whereas in the ice bag subgroups (n = 11), tm was 29.3 ± 1.3 °C (95% CI 27.7–30.8), which was significantly higher (p < 0.001). The overall 1-week survival of the experimental animals was significantly higher in the SWI elimination device subgroup (logrank p = 0.036).Conclusion. The developed device is effective in eliminating SWI of renal graft.